Do economic values and expenditures for viewing waterfowl in the U.S. differ among species?. Issue 6 (2nd November 2018) - Loomis, John; Haefele, Michelle; Dubovsky, James; Lien, Aaron M.; Thogmartin, Wayne E.; Diffendorfer, James; Humburg, Dale; Mattsson, Brady J.; Bagstad, Kenneth; Semmens, Darius; Lopez-Hoffman, Laura; Merideth, Robert
ABSTRACT: Many economic studies value birdwatching in general and often do not account for potential differences in viewers' benefits from observing different species. But, how different are economic values of viewing various bird species? To answer that question, we surveyed Ducks Unlimited (DU) members using an online questionnaire to estimate trip expenditures and consumer surplus per trip for viewing pintail ducks, waterfowl in general, and other species of waterfowl. Expenditures per trip were USD $231, $199, and $182, respectively. Consumer surpluses per trip, estimated using the contingent valuation method, were $28, $32, and $29, respectively. Neither expenditures nor consumer surplus were statistically different among species for DU members who are adept at species differentiation. Our results suggest that it may be reasonable to use a general economic value for waterfowl viewing when formulating management alternatives for a variety of waterfowl.